Effects of chlorine dioxide and ozone gases against immature stages of stored-grain insects - Li, Beibei (Kansas State University, 2019)
Utilization of ozone and chlorine dioxide has been well documented in a variety of applications, such as for treatment of drinking water, microbial inactivation in food processing settings, and for odor control. The two gases have been evaluated for managing immature stages of phosphine resistant field populations of stored-product insects. Laboratory studies were conducted to determine the effectiveness of chlorine dioxide gas against various life stages of common stored-product insect species, namely the red flour beetle, Tribolium castaneum (Herbst); lesser grain borer, Rhyzopertha dominica (Fabricius); rice weevil, Sitophilus oryzae (Linnaeus); maize weevil, Sitophilus zeamais Motschulsky; and sawtoothed grain beetle, Oryzaephilus surinamensis (Linnaeus). Several phosphine resistant field populations of these insect species were exposed to chlorine dioxide gas including phosphine susceptible laboratory populations. Target life stages were eggs (0-day-old), young larvae (14-day-old), old larvae (21-day-old), and pupae (3-day-old). Life stages were exposed to a chlorine dioxide gas concentration of 0.95 g/m³ (350 parts per million, ppm) for 2, 4, 6, 8, and 10 hours. Both phosphine resistant and phosphine susceptible populations were equally susceptible to chlorine dioxide. In general, for all species and strains mortality increased with increasing exposure time. Eggs and 14-d-old larvae were easier to kill, even at the lowest gas dosage (concentration × time product, ct product) of 1.90 g-h/m³. Although less susceptibility was observed in 21-d-old larvae and 3-d-old pupae, increased gas concentrations and/or exposure time were able to produce higher mortalities in these two stages. Progeny production of treated pupae was severely suppressed as compared to the control, indicating adverse effects of chlorine dioxide on reproductive organs. Chlorine dioxide gas can be a very effective alternative to phosphine in controlling stored-product insects associated with raw commodities. Immature stages of a phosphine susceptible laboratory strain and four phosphine resistant field strains of T. castaneum, were used for this study. Eggs, young larvae, old larvae, and pupae of T. castaneum were exposed in vials with 10 g of wheat to chlorine dioxide gas at 2.02 g/m³ (750 ppm) concentration for 2, 4, 6, and 8 h. Mortality was determined by subtracting the number of adults that emerged from the immature insects out of the total insects exposed and expressed as a percentage. Adult progeny production was determined 8 weeks after adult emergence. Complete mortality was achieved in eggs and young larvae. The highest mortality of old larvae and pupae was 86.8-95.2% and 81.1-93.8%, respectively, after an 8 h exposure. The order of susceptibility of immature stages to chlorine dioxide was: young larvae > eggs > old larvae > pupae. Mortality of immature stages increased with an increase in exposure time. At longer exposure times there was a significant reduction in progeny production, perhaps a result of higher mortality of immature stages. Adults that emerged from treated pupae revealed less progeny production. In addition, all strains of phosphine resistant insects were equally susceptible to chlorine dioxide when compared with susceptible strains. These results suggest that chlorine dioxide gas is highly effective in controlling immature life stages of laboratory and field strains of T. castaneum. Ozone was investigated as a potential alternative to control phosphine resistant strains of the lesser grain borer, Rhyzopertha dominica (F.). The efficacy of ozone against one phosphine-susceptible laboratory and two phosphine resistant field strains of R. dominica was evaluated at two concentrations (0.21 and 0.42 g/m³). Vials holding 20 adults with 0 and 10 g of wheat were exposed to each ozone concentration for up to 24 h to estimate lethal doses required for 50 (LD₅₀) and 99% (LD₉₉) mortality. After ozone exposure, mortality was assessed 5 d later. After exposure to 0.21 g/m³ of ozone for 24 h, the 5-d mortality was 77-86% with wheat and 96-97% without wheat. After exposure to 0.42 g/m³ of ozone for 16 h, the 5-d mortality with and without wheat was 100%. There were no significant differences between LD₅₀ values of the samples treated at 0.21 and 0.42 g/m³, regardless of strains and presence or absence of wheat. The small amount of wheat (10 g) affected efficacy at 0.21 g/m³, but showed a non-significant effect at 0.42 g/m³. Ozone tends to react with active sites on the surface of wheat kernels prior to reaching an effective lethal concentration for insects. High ozone concentration in the supply air reduced the time to saturate all active sites and ensured that lethal levels of free ozone were available to kill insects. Emergence of adults from eggs, young larvae, and old larvae were reduced by 96-100% relative to the emergence in the control treatment after a 72 h exposure to an ozone concentration of 0.42 g/m³. At the same concentration of ozone, pupae exposed for 2 to 10 h, had a 33 to 97% reduction in adult emergence relative to control treatment. Exposure to chlorine dioxide at concentration of 0.95 g/m³ for 3 h reduced both production and hatchability of eggs of T. castaneum and egg production of the Indian meal moth, Plodia interpunctella (Hübner). Severe effects of chlorine dioxide in both T. castaneum and P. interpunctella reproductive performance are important in terms of increase in population of these insect species after a fumigation. Population of these stored product insects is highly related to the reproductive performance of surviving insects. Sanitation of storage facilities prior to fumigation plays a critical role in the effectiveness in controlling insects due to bonding property of chlorine dioxide with organic matter.
Keywords: Chlorine dioxide; Ozone; Fumigant; Stored-product insects; Immature stages; Phosphine resistance